Critical yield-point model to estimate damage caused by brown spot and powdery mildew in barley Modelo do ponto crítico para estimar danos causados pela mancha-marrom e oídio em cevada - Agostinetto L.* (2014)
Barley (Hordeum vulgaris L.) is the second most important winter crop in Southern Brazil. The excessive rainfall in this region during the crop-growing season increases the frequency and intensity of foliar fungal diseases. The research aimed to determine the damage function equations (DFE) for the multiple pathosystem of barley brown spot and powdery mildew based on the relationship between grain yield and diseases intensity at different 'BRS Cauê' cultivar growth stages (GS) during 2009 and 2010 growing seasons in Southern Brazil. The experiments were arranged in a randomized complete block design with nine treatments and four replicates. The disease gradients were generated by strobilurins and triazols fungicides rates and number of applications on barley cv. Cauê. The fungicide applications and disease incidence and severity assessments were performed at the 22, 31, 39, 45 and 56 plant GS. The DFE were obtained by variance analysis and linear regression between grain yield and diseases intensity. Significant and negative DFE were obtained and the damage coefficients (DC) varied from 29.48 to 100.08 (2009) and from 36.08 to 113.57kg ha-1 (2010) for incidence, and from 219.5 to 6,276.6 (2009) and 102.3 to 5,292.5kg ha-1 (2010) for severity. The largest damage coefficients were obtained when diseases assessments were made on GS 22 and 31 on both growing seasons evaluated. DFE were used to calculate the economic damage threshold (EDT) as a criterion to indicate the fungicide application moment to control the diseases in cultivars similar to 'BRS Cauê' in Southern Brazil.